Pemetaan Kemampuan Bahasa Inggris Mahasiswa Non-Jurusan Berbasis CEFR melalui Englishscore - Arisandi, Vidya; Savitri, Citra; Suparman, Tarpan (SAWERIGADING, 2025)
This study aims to examine the English proficiency of non-English majors at a private university in Karawang using EnglishScore, an app-based assessment aligned with the Common European Framework of Reference for Languages (CEFR). The study employs a descriptive design combining quantitative data (descriptive statistics) with qualitative data (brief thematic analysis). Data were collected from N = 332 students through the EnglishScore app, which assessed reading, listening, grammar, and vocabulary, together with a short demographic questionnaire and brief follow-up interviews. Results indicated that 75.6% of students were at the A1 to A2 levels, with fewer reaching B1 or higher. In this study, the term “gaps” refers to the proportion of students performing below the expected proficiency for each assessed area; the largest gaps were observed in vocabulary (51.0%) and listening (29.3%). Grammar (22.3%) also required improvement, whereas reading (19.7%) showed the smallest gap. In the context of the studied program, these findings suggest the need to adapt the curriculum by prioritizing contextual vocabulary development, graded listening comprehension training, and explicit grammar instruction, alongside structured academic reading strategies, in English for General Purposes (EGP) and English for Specific Purposes (ESP) courses. AbstrakPenelitian ini bertujuan untuk meneliti kemahiran bahasa Inggris mahasiswa dari program studi non-bahasa Inggris di sebuah universitas swasta di Karawang dengan menggunakan EnglishScore, asesmen berbasis aplikasi yang selaras dengan Common European Framework of Reference for Languages (CEFR). Penelitian ini menggunakan desain deskriptif yang memadukan data kuantitatif (statistik deskriptif) dan data kualitatif (analisis tematik singkat). Data dikumpulkan dari N = 332 mahasiswa melalui aplikasi EnglishScore, yang menilai aspek membaca, menyimak, tata bahasa, dan kosakata, disertai kuesioner demografis singkat serta wawancara tindak lanjut singkat. Hasil menunjukkan bahwa 75,6% mahasiswa berada pada level A1 sampai A2, dengan proporsi yang lebih kecil mencapai B1 atau lebih tinggi. Dalam penelitian ini, istilah “kesenjangan” merujuk pada proporsi mahasiswa yang berada di bawah tingkat kemahiran yang diharapkan untuk setiap aspek yang diukur; kesenjangan terbesar ditemukan pada kosakata (51,0%) dan menyimak (29,3%). Aspek tata bahasa (22,3%) juga memerlukan perbaikan, sedangkan membaca (19,7%) menunjukkan kesenjangan paling kecil. Dalam konteks program yang diteliti, temuan ini mengindikasikan perlunya adaptasi kurikulum dengan memprioritaskan pengembangan kosakata kontekstual, pelatihan pemahaman menyimak bertingkat, dan pengajaran tata bahasa secara eksplisit, di samping strategi membaca akademik yang terstruktur, dalam mata kuliah English for General Purposes (EGP) dan English for Specific Purposes (ESP).